Transformation Of Verbal Transformation of Verbal Skills Through the Station Rotation Learning Model: A Quantitative Analysis of Students' Verbal Fluency. - lulu'ul malichah; Abdul Basith (Universitas Islam Negeri Palopo, 2026)
This study aims to examine the effectiveness of the Station Rotation Blended Learning Model in improving the maharat al-kalam (Arabic speaking skills) of 10th-grade students at MA Plus Keterampilan Hasyim Asy'ari Tegaldelimo. This study is a quasi-experimental study using a non-equivalent control group pretest-posttest design. A total of 60 10th-grade students were divided into two groups: the experimental group (n=30), which received instruction through four rotating stations (Teacher, Multimedia, Collaboration, and Creativity), and the control group (n=30), which received conventional instruction. The speaking test instrument was based on ACTFL standards. Quantitative data were analyzed using a paired-sample t-test, Cohen’s d effect size, and N-Gain. Thematic analysis of observation notes and interviews revealed increased self-confidence and reduced speaking anxiety in the experimental group. The Rotating Station Blended Learning Model proved to be effective and statistically significant in improving Arabic speaking skills. This model offers a creative solution to address low oral production skills in foreign language learning.